A Study of Outcome Reporting Bias Using Gender Differences in Risk Attitudes - Paolo Crosetto; Antonio Filippin; Janna Heider (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper exploits a large dataset of replications of the Holt and Laury (2002) risk elicitation task to study a possible outcome reporting bias using gender differences in risk attitudes. There is a strong consensus view in the experimental literature according to which women are more prudent than men in risky choices. The evidence collected in the dataset, however, does not support the consensus: only a tiny fraction of the replications displays gender differences. This striking distance between the consensus and the data gathered with this elicitation task allows us to test directly for the presence of outcome reporting bias in the risk and gender literature. We find no evidence that the likelihood of reporting about gender differences is affected by obtaining results in line or against the consensus, also controlling for authors fixed effects. The vast majority of the studies does not report gender results. The only significant determinant of the probability of reporting is the fact that the study focuses directly on the analysis of risk preferences.
Keywords: C81; D81; J16; 330; publication bias; gender difference; risk attitude